The conditional extremum lines research for the soperfluous gibbs potential surface for stratified systems - А. V. Frolkova; V. V. Illarionov; L. А. Serafimov (Тонкие химические технологии)
The possibility of a technique application revealing the probable existence area triple azeotrope, based on analysis of concentration dependences of activity coefficient complexes in liquid phases, in stratified zeotropic mixtures, mixtures containing triple homo- or heteroazeotrope has been investigated. The peculiarity of gamma-lines course in triple stratified mixtures has been estimated.